Improvement proposal model based on 5S, ABC method and SLP to improve the level of order fulfillment in a company in the commercial sector - Bravo Zuazo, Percy Esteban (2025)
The commercial sector in Peru has a sustainable growth over time, playing an important role and projecting an average growth of 3% by 2025. For this reason, commercial companies must be in constant development to be able to meet new market demands and solve new problems. In this sense, it is crucial to identify the main causes of the problems, such as the low level of order fulfillment, which is directly related to disorganization and suboptimal distributions in the warehouse, as well as high waiting times to serve customers. This research develops an improvement proposal model based on three tools (5S, ABC Method and SLP) which has as its main objective to improve the level of order fulfillment in commercial companies, in order to improve the standard time and obsolescence. The results obtained demonstrate the effectiveness of the model by increasing the order fulfillment level from 78.75% to 90%.